Social gradient in health-related quality of life among urban middle-age residents in Limassol, Cyprus: research article - Ellina, Panayiota; Middleton, Nicos; Lambrinou, Ekaterini; Kouta, Christiana (My University, 2021)
Background: Social inequalities in health threaten social cohesion and their investigation is an important research field. Monitoring the health of the population is necessary to identify health needs, design programs focused in people’s needs and to evaluate the effectiveness of health policies. Methods: A cross-sectional survey using primary data was applied. The study investigated the size and the extent of social inequalities in quality of life and health behaviours in Limassol, Cyprus. Data collection was done door-to-door in the form of survey interviews. The sample consisted of 450 residents aged 45–64 across 45 randomly selected neighbourhoods, that met the selection criteria. The tools used were: Demographic questionnaire, SF 36 Questionnaire, IPAQ- International Physical Activity Questionnaire short form. Results: The social gradient appears in all social indicators. Physical dimension of health has a strong relationship between health-related quality of life with the education index. Specifically, the range is 12 points for males and 14 points for females (p for interaction = 0.16). Profession systematically appears to have a stronger relationship with men than with women, and is present in both physical and mental dimensions. The range is 13 points for men and 10 points for women (p for interaction = 0.31). Conclusions: It seems that young highly educated males, employed full time, earning high income and engaging in mild physical activity, have significantly higher level of health-related life quality, compared to other middle age adult groups, living in Limassol. This finding is in agreement with other studies that show correlations between gender and the patterns of risk factors.
Keywords: Social inequalities; Quality of health; SF 36; Social status; Gender